(untitled) (Research, Society and Development, 2022)
Hyperhidrosis is a pathology associated with excessive sweat production, due to sweat gland dysfunction. There are several forms of treatment, which, for different reasons, have associated problems. Recently, the use of Botulinum Toxin as a form of treatment has become widespread, as it is a minimally invasive procedure, with low possibility of side effects, and reasonable duration of results. Thus, this study aimed to evaluate the effectiveness of botulinum toxin application in cases of hyperhidrosis, as well as its positive impact in relation to other forms of treatment. Therefore, an integrative literature review was carried out, through the systematization of 16 studies, which were published in the last 5 years, in Portuguese and English. The results found allowed the realization of a discussion about aspects about the pathophysiology of hyperhidrosis, the action of botulinum toxin and its use in the treatment of hyperhidrosis. It was concluded that botulinum toxin has a relevant therapeutic potential in the treatment of hyperhidrosis.